Development of Holland Based Career Module as a Career Guidance and Counseling Design for High School Students - Hulukati, Wenny; Smith, Mardia Bin; Puluhulawa, Meiske; Jannah, Dian Hilyatul (Bisma The Journal of Counseling, 2022)
This study aims to create a Holland-based career guidance and counseling module as a guide in designing career guidance and counseling for high school students in Gorontalo Province. This study uses research and development methods consisting of several steps: defining potentials and problems, data collection, product design, design validation, revision, and product testing. Referring to qualitative research, the data obtained came from expert validation questionnaires and product test questionnaires. This development study eventually created a Holland-based career guidance and counseling module. This module can be used by Guidance and counseling teachers as a career design guide because it has passed the expert validation test from guidance and counseling experts, language experts, and learning media design experts.